Ecologia trófica e ecomorfologia da ictiofauna de igarapés maranhenses (Alcântara-MA) - Reis, Andressa da Silva (2011)
The trophic ecology is one of the most important aspects to understand the role of a species in the community and in the ecosystem functioning. Studies regarding the feeding of fishes coupled to the ecomorphology of a species become important tools in understanding their ecological role and position in the environment. The present study aimed to analyze the types and amount of food consumed by eleven species of fishes collected in six streams of Alcântara, Maranhão state, and assess their possible interspecific interactions. The specimens were collected in the rainy season, in January, and in the dry season, in November 2008. The analysis of morphology of the fish species was performed by measuring 17 characteristics and calculating 16 ecomorphological attributes. Analysis of the contents of the digestive tract was performed quantitatively and qualitatively. In order to determine the feeding habits of each species the frequency of occurrence, volume and alimentary index of each food item consumed were calculated. The majority of individuals analyzed was collected in the streams Igarapé do Camarajó and Igarapé do Brito. The trophic structure of fish assemblages of these two streams was diversified in both, rainy and dry seasons. The habit of the benthivore species Micropoecilia cf. parae and Apistogramma cf. piauienses was corroborated by their morphology. In the rainy season, there was a higher niche overlap in the diet of insectivorous species in the stream Igarapé do Camarajó, but the morphology of these species showed distinct spatial occupation of the habitat, thus allowing their coexistence. In the dry season most species had food overlap due to the consumption of organic detritus in the Igarapé do Camarajó stream and due to the consumption of chironomid larvae in the Igarapé do Brito stream. Fishes of Camarajó and Brito streams were more likely to feeding specialization in the rainy season and increased diversification of the items consumed during the dry season, indicated, respectively, by larger and smaller niche breadth. The changes in the trophic structure, in the niche overlap and in the niche breadth of fish community in the six streams studied indicate that fluctuations on the hydrological cycle in these streams are an important factor in the throphic dynamics of these fish communities.